Notes on Caliscelidae from Turkey, with First Record of the Tribe Adenissini Dlabola (Hemiptera, Fulgoromorpha) - Gnezdilov, Vladimir M.; Özgen, Inanç (American Entomological Society, 2024)
Caliscelidae records from Turkey are summarized. The tribe Adenissini Dlabola is recorded for the first time from the country after Perissana bispinata (Dlabola, 1980) collected in Mardin Province. New records for Ommatidiotus iranicusHorváth, 1905 and Bruchoscelis peculiaris (Horváth, 1904) are given. © 2024 American Entomological Society. All rights reserved.
Keywords: Adenissina; Bruchoscelis; new record; Ommatidiotus; Perissana; planthopper